The Croatian Diaspora - Grbić, Jadranka (Array, 2000)
Croatian state and ethnic territory was traditionally a territory of emigration. Following to the numerous push and pull factors, almost myriads of people moved to various European and overseas countries. The result of this are the Croatian migrant communities around the world, but also many depopulated areas in Croatian territory.